Energetic, economic, and environmental perspectives on systematic design and energy management of a power-to-methane system integrated with power cycle - Saebea, Dang; Arpornwichanop, Amornchai; Patcharavorachot, Yaneeporn (My University, 2025)
The methanation process transforms CO2 into green methane by combining it with hydrogen from solid oxide electrolysis cells (SOECs). Efficient energy management of the integrated system, along with effective heat utilization from methanation for power generation, enhances system efficiency. This study compares four configurations of a system incorporating SOECs, methanation, and the Rankine cycle, focusing on energetic, economic, and environmental performance. The impact of gas recycling in the adiabatic methanator on system performance was also investigated. Key findings reveal that incorporating a water separation unit and increasing the gas recycle ratio significantly improve methane yield and CO2 utilization. Systems with water removal through heat integration achieve overall efficiencies of 50.17 to 52.27%. The levelized product cost of the system with water removal is lower, ranging from 195.27 to 223.05 $/MWh, and it produces the lowest CO2 emission intensity at 119.91 kgCO2 per MWhCH4.
Keywords: Adiabatic methanator; CO2 utilization; Economic analysis; Green methane production; Solid oxide electrolysis cells